Codes of ethics and codes of conduct for using ICT in education - Pivec, Franci (Organizacija (Kranj), 2011)
Codes of conduct (and ethical codes) are a way of ensuring that positive impact in the community prevails. Higher education environments that have standardized ICT management show higher quality of performance if compared to those who have not. Also characteristic for these environments is their strong willingness for change. A university is a place of scientific communication and, thus, ICT and especially the Internet represent access to a new development phase to which the best universities are strongly dedicated. In this way, also ethics returns to the core of the mission undertaken by higher education institutions. Many countries around the world are adopting National Educational Technology Standards (NETS), which have been developed and are continuously updated within the ISTE Association and at the same time represent a code of conduct for students, teachers, administrators and all others involved in high-quality study. These standards must be supported with code of ethics, because they depend on considerations of important moral values.
Keywords: education; izobraževanje; visoko šolstvo; communication; komuniciranje; informacijska tehnologija; information technology; komunikacijska tehnologija; uporaba; standardi; poslovna etika; etični kodeksi